PPKM (Pengembangan Perangkat berbasis Kurikulum MBKM) as the Practice of Distance Learning in the Course of Statistical Method - Dian Ratna Puspananda; Dwi Erna Novianti; Ayu Fitrianingsih (Jurnal Pendidikan Edutama, 2022)
Abstract: The covid-19 pandemic causes the need of distance learning. As in offline learning, its learning objectives have to be fulfilled. In the learning process, lesson plan is very important. The aim of this study is to develop the MBKM based lesson plan as the implementation of distance learning. The method of this study is research and development which implements the development model of Thiagarajan that is modified into three stages, namely: define, design, and develop stages. The methods in collecting data are documentations, questionnaires, and achievement tests. Based on the analysis results, the modification of developed learning tools using 4-D model produces MBKM based learning tools which is implemented in the distance learning using Moodle. The learning tools are valid based on the experts and the results of pretest that show the positive responses on learning and the achievement results that fulfilled the criteria of validity, reliability, and sensitivity test items.   Abstrak: Pandemi covid-19 menyebabkan perlunya pembelajaran jarak jauh. Seperti dalam pembelajaran offline, capaian pembelajaranpun harus terpenuhi. Dalam proses pembelajaran, RPP sangatlah penting. Penelitian ini bertujuan untuk mengembangkan RPP berbasis MBKM sebagai implementasi pembelajaran jarak jauh. Metode penelitian ini adalah penelitian dan pengembangan yang mengimplementasikan model pengembangan Thiagarajan yang dimodifikasi menjadi tiga tahap, yaitu: tahap define, design, dan develop. Metode pengumpulan data dengan dokumentasi, angket, dan tes prestasi. Berdasarkan hasil analisis, modifikasi perangkat pembelajaran yang dikembangkan menggunakan model 4-D menghasilkan perangkat pembelajaran berbasis MBKM yang diimplementasikan dalam pembelajaran jarak jauh menggunakan Moodle. Perangkat pembelajaran tersebut valid berdasarkan ahli dan hasil pretest yang menunjukkan respon positif terhadap pembelajaran dan hasil pencapaian yang memenuhi kriteria validitas, reliabilitas, dan sensitivitas item tes.